EVALUATING THE IMPACT OF THE MANAGEMENT OF CREDIT RISK, MARKET RISK AND LIQUIDITY RISK ON THE PERFORMANCE OF BANKS IN NIGERIA - Ahmed Oluwatobi ADEKUNLE (Gusau Journal of Accounting and Finance, 2025)
This study examines the impact of credit risk management, market risk management, and liquidity management on bank profitability, with Earnings per Share (EPS) serving as the key performance measure. Using panel data and employing both fixed and random effects models, the analysis finds that credit risk indicators specifically, the ratio of non-performing loans to loans and advances (NPLLA) and the ratio of loan loss provisions to total assets (LLPTA) - have a significant negative effect on bank earnings. In contrast, measures of financial intermediation efficiency, such as the loans-to-deposits ratios (LATD and TDLA), show a positive and significant relationship with EPS. Market risk, particularly foreign exchange volatility (FER), negatively influences profitability, while liquidity management indicators, aside from bank size (BKS), are not significant predictors of EPS. The Hausman test confirms the suitability of the random effects model, which provides a stronger explanatory power. The findings highlight the critical importance of robust credit risk management, effective foreign exchange risk mitigation, and strategic bank growth in enhancing earnings performance. Policy implications suggest that banks should strengthen risk assessment practices, regulators should enforce higher supervisory standards, and strategic consolidation in the sector should be encouraged. Overall, the study offers valuable insights for both practitioners and policymakers aiming to improve the financial health and stability of the banking sector.